Evidence for Cleavage of the Metalloprotease Vsm from Vibrio splendidus Strain JZ6 by an M20 Peptidase (PepT-like Protein) at Low Temperature - Liu, Rui; Qiu, Limei; Cheng, Qi; Zhang, Huan; Wang, Lingling; Song, Linsheng (Frontiers in Microbiology, 2016)
Metalloprotease Vsm is a major extracellular virulence factor of Vibrio splendidus. The toxicity of Vsm from V. splendidus strain JZ6 has been characterized, and production of this virulence factor proved to be temperature-regulated. The present study provides evidence that two forms (JZE1 and JZE2) of Vsm protein exist in extracellular products (ECPs) of strain JZ6, and a significant conversion of these two forms was detected by SDS-PAGE and immunoblotting analyses of samples obtained from cells grown at 4, 10, 16, 20, 24 and 28 ℃. Mass spectroscopy confirmed that JZE1 was composed only of the peptidase_M4 domain of Vsm, and JZE2 contained both the PepSY domain and the peptidase_M4 domain. An M20 peptidase T-like protein (PepTL) was screened from the transcriptome data of strain JZ6, which was considered as a crucial molecule to produce the active Vsm (JZE1) by cleavage of the propeptide. Similar to that of Vsm, PepTL mRNA accumulation was highest at 4 ℃ (836.82-fold of that at 28 ℃), decreased with increasing of temperature and reached its lowest level at 28 ℃. Deletion of the gene encoding the PepTL resulted in a mutant strain that did not produce the JZE1 cleavage product. The peptidase activity of PepTL recombinant protein (rPepTL) was confirmed by cleaving the Vsm in ECPs with an in vitro degradation reaction. These results demonstrate that PepTL participates in activating Vsm in strain JZ6 by proteolytic cleavage at low temperature.